Analysis of the excited bottom and bottom-strange states B1(5721), B2⃰(5747), Bs1(5830), Bs2⃰(5840), BJ(5840) and BJ(5970) of the B meson family *Supported by the Fundamental Research Funds for the Central Universities (2016MS133) and Natural Science Foundation of HeBei Province (A2018502124). (March 2020) - Yu 于, Guo-Liang 国梁; Wang 王, Zhi-Gang 志刚
Abstract: In order to make a further confirmation of the assignments of the excited bottom and bottom-strange mesons, , and and identify possible assignments of and, we study the strong decay of these states with the decay model. Our analysis supports the assignments of and as the and states, and and as the strange partners of and . Besides, we tentatively identify the recently observed and as the and states. It is noted that these conclusions need further confirmation by measurements of the decay channels and .